2021
DOI: 10.3390/microorganisms9091974
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota of Cow’s Milk with Udder Pathologies

Abstract: Mastitis is the most common disease for cattle, causing great economic losses for the global dairy industry. Recent studies indicate the multi-agent and microbiome diversity of this disease. To understand the nature of mastitis and investigate the role of the microbiome in the development of pathologies in the udder of bovines, we performed NGS sequencing of the 16S rRNA gene of cow’s milk with pathologies of the udder. The obtained data show a significant increase in the Cutibacterium, Blautia, Clostridium se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 43 publications
1
12
0
1
Order By: Relevance
“…Among this genus, Staphylococcus Coagulase-Negative (SCN) and Staphylococcus aureus are the most frequently diagnosed causes of subclinical and clinical IMI in goats, respectively ( Contreras et al, 2007 ; Dore et al, 2016 ). Previous studies have also found this genus in the milk microbiota of humans ( Hunt et al, 2011 ; Fernández et al, 2020 ; Gryaznova et al, 2021 ), cows ( Oikonomou et al, 2012 , 2014 ) and healthy goats ( Deinhofer and Pernthaner, 1995 ; Zhang et al, 2017 ; Polveiro et al, 2020 ). On the other hand, even though this agent is present in animals with mastitis or healthy animals, the species of Staphylococcus sp.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Among this genus, Staphylococcus Coagulase-Negative (SCN) and Staphylococcus aureus are the most frequently diagnosed causes of subclinical and clinical IMI in goats, respectively ( Contreras et al, 2007 ; Dore et al, 2016 ). Previous studies have also found this genus in the milk microbiota of humans ( Hunt et al, 2011 ; Fernández et al, 2020 ; Gryaznova et al, 2021 ), cows ( Oikonomou et al, 2012 , 2014 ) and healthy goats ( Deinhofer and Pernthaner, 1995 ; Zhang et al, 2017 ; Polveiro et al, 2020 ). On the other hand, even though this agent is present in animals with mastitis or healthy animals, the species of Staphylococcus sp.…”
Section: Discussionmentioning
confidence: 70%
“…In this study, the milk of goats was mainly colonized by the phyla Firmicutes, Bacteroidetes, Actinobacteria, and Proteobacteria; they have also been found in the milk of other goats ( Zhang et al, 2017 ), cows ( Gryaznova et al, 2021 ), humans, and in human intestines ( Urbaniak et al, 2016 ; Rinninella et al, 2019 ). Changes in the phylum Proteobacteria, as demonstrated here in the milk of healthy animals, in relation to subclinical mastitis, in the human microbiota are related to some population signatures in the microbiota in diseases ( Rizzatti et al, 2017 ).…”
Section: Discussionmentioning
confidence: 72%
“…Inflammation of the udder tissue has a negative impact on economical milk production and the animal’s welfare due to pathologies causing edema, swelling, pain, inflammation, or udder fibrosis [ 92 ] and to a reduced reproductive efficiency [ 93 ]. Disease control is hindered by the causes of multifactorial occurrence and involving a large number of pathogens [ 94 ]. The main pathogens inducing mastitis are S. aureus , Streptococcus uberis , and Streptococcus dysgalactiae [ 95 , 96 , 97 ] and more often isolated strains of E. coli [ 98 ].…”
Section: Prevention Of Udder Infections In Cattle With Particular Emphasis On Bacterioci Like-substancementioning
confidence: 99%
“…This invading encroachment is favoured by the compromised immune status of the host and the interactions between the opportunistic pathogens and the resident microbiota of the mammary gland [ 5 , 7 11 ]. Depending on the host–pathogen interactions [ 12 14 ], bovine mastitis can manifest clinical features of apparent changes in the color of milk, swelling, redness, warmth and pain in the affected udder, systemic symptoms like fever and anorexia and sometimes death due to toxemia [ 15 , 16 ]. Despite intensive research and implementation of various strategies over the last few decades to manage mastitis, the control of this dairy disease is still elusive because of the dynamic changes in the etiology [ 3 ].…”
Section: Introductionmentioning
confidence: 99%